Konsep Islamic Ethic Marketing di Perbankan Syariah - Cipta, Hendra (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2019)
Marketing is part of muamalah in Islam which if carried out based on Islamic ethical norms based on the Qur'an and hadiths will become worship even though marketing is not related to mahdah worship. The article describes the concept of marketing based on Islamic ethics, also known as Islamic morals. The concept of Islamic ethic marketing is offered in the hope that it can be applied in marketing Islamic banks because it is based on the principle of welfare. This concept is offered so that future marketing operations of Islamic banks welfare (falah) in terms of education and protection for the welfare of the community.